Monitoring Nyeri dengan Kamera Termal pada Pasien Cedera Kepala dengan Terapi Es Batu di RSUP dr. Wahidin Sudirohusodo Makassar - Suhatman A.Hakim; Elly L.Sjattar; Muh.Nasrum Massi (Jurnal Kesehatan Manarang, 2020)
Headache is the most common somatic disorder in patients after head injury (29-54%). The use of acupuncture points has been used, especially in China in treating various health problems such as headaches. This study aims to determine the effect of ice cube therapy at Feng Fu GV 16 point on decreasing pain in patients with Head Injury who have Post Traumatic Headache in RSUP DR Wahidin Sudirohusodo Makassar with thermal camera monitoring indicators and VRS. This study uses the quasy experiment method. Sampling with accidental sampling with a total sample of 30 people (15 controls and 15 experimental groups). The experimental group was given analgesic + ice therapy at GV Feng Fu 16 point while the control group was only given analgesic. Data was tested by the Independent T Test statistical test with a confidence level of 95%. All data were analyzed using the SPSS version 21.0 program (SPSS, Inc. Chicago, IL). Mean changes in VRS intervention group (1.20 ± 0.56) and control group (0.80 ± 0.56) and mean changes in facial temperature with thermal camera monitoring of the intervention group (1.48 ± 5, 09) and the control group (0.93 ± 1.71). There was no difference in changes in VRS (p: 0.061) and Face Scale (p: 0.698) between the intervention group and the control group. Giving ice cube at Feng Fu GV 16 point is not significant to reduction of pain in Head Injury patients who experience Post Traumatic Headache with VRS indicators and facial temperature with thermal camera monitoring compared to control group. By that, for practitioners in hospitals to be able to increase knowledge related to ice cube therapy at Feng Fu GV 16 point in reducing pain.